2022
DOI: 10.1371/journal.pone.0262041
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the umbilical cord in fetal growth restriction and preeclampsia

Abstract: Fetal growth restriction (FGR) is associated with adverse perinatal outcomes. Pre-eclampsia (PreE) increases the associated perinatal morbidity and mortality. The structure of the umbilical cord in the setting of FGR and PreE is understudied. This study aimed to examine changes in the umbilical cord (UC) composition in pregnancies complicated by FGR and FGR with PreE. UC from gestational age-matched pregnancies with isolated FGR (n = 5), FGR+PreE (n = 5) and controls (n = 5) were collected, and a portion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…However, other biological processes, such as electron transport chain and nucleotide metabolic and catabolic processes were also enriched, while the pro-teins the lowest fold change in IUGR versus AGA were predominantly involved in platelet degranulation and aggregation, cell adhesion and regulation of response to stimulus. These findings agree with previous studies that identified platelet activation and extracellular matrix remodeling in fetal growth restriction [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, other biological processes, such as electron transport chain and nucleotide metabolic and catabolic processes were also enriched, while the pro-teins the lowest fold change in IUGR versus AGA were predominantly involved in platelet degranulation and aggregation, cell adhesion and regulation of response to stimulus. These findings agree with previous studies that identified platelet activation and extracellular matrix remodeling in fetal growth restriction [21].…”
Section: Discussionsupporting
confidence: 93%
“…Several proteins identified in our cohort (e.g., CAT, HBG1, PKM, PNP, S100A8, IDH1) were previously reported to be associated with fetal growth restriction using either maternal or cord plasma [12,15,21]. IUGR is associated with impaired nutrient and/or oxygen delivery that may leave the mononuclear cells in cord plasma, fetal organs and placenta more susceptible to damage and leakage of cytosolic proteins consistent with the increased levels of proteins such as CAT in IUGR cord plasma [12,15,24,25].…”
Section: Discussionmentioning
confidence: 74%
“…Maternal diseases such as preeclampsia (PE) may be associated with fetal growth restriction (FGR), in turn resulting in a higher risk of adverse obstetric and perinatal outcomes such as stillbirths or long-term morbidity [8][9][10]. A recent proteomic investigation demonstrated that in fetuses with FGR or PE with superimposed FGR, the most significant changes occurring to the umbilical cord involved proteins associated with Wharton's jelly and inflammatory and angiovascular processes [11].…”
Section: Introductionmentioning
confidence: 99%
“…One of the promising diagnostic methods is comparative proteomics based on the analysis of the protein profile in normal and abnormal tissues (29). Reviews have highlighted the proteomic approaches that have been used to explore pre-eclampsia (PE), FGR and preterm birth (30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%